Return to work following laparoscopic‐assisted resection or open resection for rectal cancer: Findings from AlaCaRT—Australasian Laparoscopic Cancer of the Rectum Trial. (6th December 2020) - Law, Chi Kin; Brewer, Kate; Brown, Chris; Wilson, Kate; Bailey, Lisa; Hague, Wendy; Simes, John R.; Stevenson, Andrew; Solomon, Michael; Morton, Rachael L.; ,
Abstract: Background: Maintaining employment for adults with cancer is important, however, little is known about the impact of surgery for rectal cancer on an individual's capacity to return to work (RTW). This study aimed to determine the impact of laparoscopic vs. open resection on RTW at 12 months. Methods: Analyses were undertaken among participants randomized in the Australian Laparoscopic Cancer of the Rectum Trial (ALaCaRT), with work status available at baseline (presurgery), and 12 months. Multivariable logistic regression, adjusted for sociodemographic and clinical characteristics estimated the effect of surgery on RTW in any capacity, or return to preoperative work status at 12 months. Results: About 228 of 449 (51%) surviving trial participants at 12 months completed work status questionnaires; mean age was 62 years, 66% males, 117 of these received laparoscopic resection (51%). Of 228, 120 were employed at baseline (90 full‐time, 30 part‐time). Overall RTW in 120 participants in paid work at baseline was 78% (84% laparoscopic, 70% open surgery). Those employed full‐time were more likely to RTW at 12 months (OR, 3.55; 95% CI, 1.02–12.31). Those with distant metastases at baseline were less likely to RTW (OR, 0.07; 95% CI, <0.01–0.83). Laparoscopic surgery was associated with a higher rate of RTW but did not reach statistical significance (OR 2.88; 95% CI, 0.95–8.76). Conclusions: Full‐time work presurgery and the presence of metastatic disease predicts RTW status at 12 months. A laparoscopic‐assisted surgical approach to rectal cancer may facilitate more patients to RTW, however, larger sample sizes are likely needed to confirm this result. Abstract : Rectal cancer patients with laparoscopic‐assisted surgery have a slightly but not significantly higher return to work rate at 12 months than those with open rectal resection. Results of this randomised controlled trial highlight the importance of discussing employment disruption and retention strategies with adults undergoing surgery for rectal cancer